(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: Cardiac resynchronisation therapy with defibrillator backup (CRT-D) is an established therapeutic option in selected heart failure patients. Data on its pronounced long-term outcome are scarce. We evaluated the long-term outcome (>5 years) of patients with the main focus on device-associated events. METHODS: Out of a prospective CRT-D registry with 219 patients, all 49 patients (22%) who survived for at least 5 years were analysed. Baseline characteristics, device associated issues (battery longevity, lead problems, phrenic nerve stimulation, infections and pacing threshold levels), implantable cardioverter-defibrillator (ICD) therapies, mortality, changes in left ventricular ejection fraction (LVEF) and improvement in New York Heart Association (NYHA) class were considered. RESULTS: The mean ± standard deviation age of the patients was 63±10 years and follow-up was 84±18 months. Seventy-eight percent were male, 73% had nonischaemic cardiomyopathy and 80% a primary prevention indication. After initially surviving 5 years, 8 patients (16%) died during further follow-up. LVEF improved from 23%±7% to 35%±13% (p-value <0.0001) at last follow-up. 14 patients (29%) had appropriate ICD therapy, mainly for ventricular tachycardia. No first-ever arrhythmic event occurred beyond year 4.5. Device longevity was 54±13 months. Twenty-three technical problems occurred in 20 patients (40%), 14 of whom (61%) required surgery (7 lead defects, 4 dislodgments, 3 others). Dislodgements occurred early (after 2±2 months); defects were scattered (2–59 months) during follow-up. CONCLUSION: Selected patients who survive for at least 5 years experience sustained improvement in LVEF and NYHA- class and only few arrhythmic episodes. Technical problems occur in 40% of patients (60% requiring surgery), mainly shortly after implant and again after 4 to 5 years.